MOTORISTS CHANGE BEHAVIOURAL ANALYSIS ON SCHOOL SAFETY ZONE PROJECT (CASE STUDY: SMP NEGERI 9 KOTA LANGSA, ACEH) - Bukit, Ipak Neneng Mardiah; Ismida, Yulina (JURNAL TEKNIK SIPIL, 2018)
Abstract: School Safety Zone (ZoSS) is a road area in front of school where vehicles must reduce speed in time basis. The purpose of SSZ is to ensure students safety during school hours, especially when school started and ended. Kota Langsa is one district in Aceh Province where applied city administrative sistem since 2001. It is developing in every sector, including transportation infrastructure. However, the ZoSS is not applied optimally thus, this zone is not well known to the public. This paper aims to study whether the zone will change the street users behavior and vehicles reduce speed when going through the school zone. The research uses Z-score testing method from norm standard distribution for ZoSS application requirements. The test is done in 8 (eight) roads in front school yard with no school zone facilities. Furthermore, one school is selected to develop minimum ZoSS facilities. The evaluation of the street users from both conditions (with and without ZoSS) shows changing from unsafe to safety. That means the ZoSS gives a positive changes to the street users behavior.Keywords : Behavior, Safety, School, Speed, Street Users, ReduceAbstrak: Zona Selamat Sekolah (ZoSS) adalah ruas jalan di depan sekolah yang mengatur kendaraan yang melewatinya harus mengurangi kecepatan berbasis waktu, dan kemudian peraturan itu enjadi aturan etika bagi pengguna jalan. Namun demikian, masih banyak pengendara yang tidak memahami etika tersebut. Kota Langsa adalah salah satu Kota di Provinsi Aceh yang menerapkan sistem Kota Administrasi sejak tahun 2001. Kota ini terus berkembang di berbagai sektor, termasuk dalam pembangunan infrastruktur transportasinya. Akan tetapi ZoSS masih belum diaplikasikan secara optimal sehingga tidak terlalu dikenal oleh masyarakat. Artikel ini bertujuan untuk mempelajari apakah jika ZoSS diterapkan di Kota Langsa ini akan merubah perilaku pengendara yang lewat di depan sekolah dengan mengurangi kecepatan kendaraannya atau tidak. Penelitian ini menggunakan metode uji Z-Score pada standar distribusi normal untuk kebutuhan ZoSS. Uji Z ini dilakukan di 8 wilayah sekolah yang belum terdapat fasilitas ZoSS. Selanjutnya pada salah satu sekolah dilakukan eksperimen dengan membangun fasilitas minimum sementara. Hasil dari evaluasi menunjukkan perubahan perilaku pengguna jalan dari belum selamat menjadi selamat. Artinya fasilitas ZoSS memberikan pengaruh positive terhadap perilaku pengguna jalan.Kata kunci : Perilaku, Pengguna jalan, Selamat, Sekolah, Pengurangan, Kecepatan.